CDKN2A promoter methylation is related to the tumor location and histological subtype and associated with Helicobacter pylori flaA(+) strains in gastric adenocarcinomas - Santos Alves, Markenia Kelia; Lima, Valeska Portela; Ferrasi, Adriana Camargo [UNESP]; Rodrigues, Maria Aparecida Marchesan [UNESP]; Pardini, Maria Ines de Moura Campos [UNESP]; Barem Rabenhorst, Silvia Helena (Wiley-Blackwell Publishing, Inc, 2010)
Promoter hypermethylation of CDKN2A (p16INK4A protein) is the main mechanism of gene inactivation. However, its association with Helicobacter pylori infection is a controversial issue. Therefore, we examined a series of gastric adenocarcinomas to assess the association between p16INK4A inactivation and H. pylori genotype (vacA, cagA, cagE, virB11 and flaA) according to the location and histological subtype of the tumors. p16INK4A expression and CDKN2A promoter methylation were found in 77 gastric adenocarcinoma samples by immunohistochemistry and methylation-specific PCR, respectively. Helicobacter pylori infection and genotype were determined by PCR. A strong negative correlation between immunostaining and CDKN2A promoter region methylation was found. In diffuse subtype tumors, the inactivation of p16INK4A by promoter methylation was unique in noncardia tumors (p = 0.022). In addition, H. pylori-bearing flaA was associated with non-methylation tumors (p = 0.008) and H. pylori strain bearing cagA or vacAs1m1 genes but without flaA was associated with methylated tumors (p = 0.022 and 0.003, respectively). Inactivation of p16INK4A in intestinal and diffuse subtypes showed distinct carcinogenic pathways, depending on the tumor location. Moreover, the process of methylation of the CDKN2A promoter seems to depend on the H. pylori genotype. The present data suggest that there is a differential influence and relevance of H. pylori genotype in gastric cancer development.
Keywords: p16INK4A; gastric cancer; histological subtypes; tumor location; methylation; Helicobacter pylori genotypes